2016
DOI: 10.1002/mpr.1501
|View full text |Cite
|
Sign up to set email alerts
|

Use of a two‐phase process to identify possible cases of mental ill health in the UK military

Abstract: Two-phase mental health screening methods, in which an abridged mental health measure is used to establish who should receive a more comprehensive assessment, may be more efficient and acceptable to respondents than a stand-alone complete questionnaire. Such two-phase methods are in use in US armed forces post-deployment mental health screening. This study assesses the sensitivity and specificity of abridged instruments (used in the first phase) compared to the full instruments (the second phase), and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We have previously reported that the two-stage questionnaire reduced resource burden without substantial loss of sensitivity for PTSD. 17 For the secondary outcomes we included a question from the short form-36 (SF-36) to assess functional impairment 18 and a modified version of the Brief Traumatic Brain Injury Screening schedule exploring possible symptoms associated with injury; these symptoms were losing consciousness, being dazed or confused, not remembering the injury and symptoms of concussion (e.g. headache and dizziness).…”
Section: Measures At Baseline First Stage-assessmentmentioning
confidence: 99%
“…We have previously reported that the two-stage questionnaire reduced resource burden without substantial loss of sensitivity for PTSD. 17 For the secondary outcomes we included a question from the short form-36 (SF-36) to assess functional impairment 18 and a modified version of the Brief Traumatic Brain Injury Screening schedule exploring possible symptoms associated with injury; these symptoms were losing consciousness, being dazed or confused, not remembering the injury and symptoms of concussion (e.g. headache and dizziness).…”
Section: Measures At Baseline First Stage-assessmentmentioning
confidence: 99%
“…To increase the probability of the development of psychiatric syndromes, a sub-sample of 591 subjects was selected for interview, with two-thirds consisting of high scorers (defined by the 85 th percentile or higher of the global severity index [GSI] of the SCL-90) and a random sample of those with scores below the 85 th percentile. Such a two-phase procedure, consisting of initial screening and subsequent interview with a stratified high-risk sub-sample, is a recommended approach in epidemiologic research (Burdett et al, 2016;Dunn et al, 1999). Altogether, seven interview waves were conducted : in 1979 (m=292; f=299), 1981 (m=220; f=236), 1986 (m=225; f=232), 1988 (m=200; f=224), 1993 (m=192; f=215), 1999 (m=162; f=205), and 2008 (m=144; f=191).…”
Section: Participants and Sampling Proceduresmentioning
confidence: 99%
“…6 Therefore, more comprehensive valuation is recommended, including two-phase case-finding techniques. 7 The relevance of depression in medical patients is supported by outcome studies showing that it impairs healthrelated quality of life and is associated with increased costs, 8 decreased compliance with medical treatment, 3 and impairment of the outcome of medical conditions. 9 Particularly relevant is the fact that depression has been linked with higher mortality rates in different medical illnesses, and the increased mortality rate persists when controlling for different risk factors, which include both biological factors and unhealthy behaviours.…”
Section: Introductionmentioning
confidence: 99%